2010
DOI: 10.1175/2010jcli3701.1
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic and Elemental Changes in Winter Snow Accumulation on Glaciers in the Southern Alps of New Zealand

Abstract: The authors present stable water isotope and trace element data for fresh winter snow from two temperate maritime glaciers located on opposite sides of the New Zealand Southern Alps. The isotopes d 18 O and dD were more depleted at the eastern Tasman Glacier site because of prevailing westerly flow and preferential rainout of heavy isotopes as air masses crossed the Alps. The deuterium excess provided some indication of moisture provenance, with the Tasman Sea contributing ;70% of the moisture received at Fran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
(71 reference statements)
0
20
0
Order By: Relevance
“…(NIWA, 2009). The Tasman Sea has been identified as a major contributor to snow accumulation on Tasman Glacier due to prevailing westerly flow (Purdie et al, 2010). Therefore mean monthly Sea Surface Temperature (SST) for the Tasman Sea were derived from gridded NCEP/NCAR reanalysis (Kalnay et al, 1996;Kistler et al, 2001).…”
Section: Climate-accumulation Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…(NIWA, 2009). The Tasman Sea has been identified as a major contributor to snow accumulation on Tasman Glacier due to prevailing westerly flow (Purdie et al, 2010). Therefore mean monthly Sea Surface Temperature (SST) for the Tasman Sea were derived from gridded NCEP/NCAR reanalysis (Kalnay et al, 1996;Kistler et al, 2001).…”
Section: Climate-accumulation Relationshipsmentioning
confidence: 99%
“…However, some potential markers are more likely to stay in situ than others, for example fine dust particles may persist while soluble ions are removed (Raben and Theakstone, 1994;Kameda et al, 2003); and useful climate information was found to persist in an ice core retrieved from Baffin Island, Canada, a site with significant melting (Fisher et al, 1998;GotoAzuma et al, 2002). The potential to derive net accumulation data from ice cores retrieved from New Zealand glaciers is yet to be fully explored, although information pertaining to moisture provenance is found in fresh winter snow (Purdie et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…gov/HYSPLIT.php. This model relies on gridded meteorological data and has been used in other studies to examine the effects of the vapour pathways on precipitation, for example, in North America (Strong et al, 2007;Sjostrom and Welker, 2009;Ersek et al, 2010) and in the Alps and the New Zealand (Purdie et al, 2010). Uncertainties in the calculated back trajectories increase over time and the dominant pathways of a storm may not necessarily be reflected in the route of an advected air mass (Helsen et al, 2007); therefore, caution is required in trajectory interpretations, particularly on synoptic time scales.…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…This is because several of these factors simultaneously influence the isotopic composition of the individual rainfall events to different and varying extent. In fact, many of the studies involving isotopes have implicitly relied on backward wind trajectories for identifying the water vapour source areas (Strong et al, 2007;Sjostrom and Welker, 2009;Breitenbach et al, 2010;Ersek et al, 2010;Purdie et al, 2010). Some of these studies have also introduced isotope systematics to the gridded atmospheric data to explain the causality of the observed isotopic variations using general atmospheric circulation models (GCMs; Joussaume et al, 1984;Jouzel et al, 1987;Hoffmann et al, 2000;Yoshimura et al, 2003;Yoshimura et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation